Carboplatin, doxorubicin and etoposide in the treatment of tumours of unknown primary site - Piga, A (Nature Publishing Group, 2004)
The aim of this study was to assess the activity and toxicity of a platinum-based treatment on a group of patients with unknown primary tumours (UPTs). Patients with a diagnosis of UPT underwent a standard diagnostic procedure. Treatment was started within 2 weeks from diagnosis and consisted of carboplatin 400 mg m(−2) day 1, doxorubicin 50 mg m(−2) day 1, etoposide 100 mg m(−2) days 1–3, every 21 days. Response was evaluated after three courses and treatment continued in case of objective response (OR) or symptom control. A total of 102 patients were eligible. The median age was 59 years, sex male/female 54/48, histology was mainly adenocarcinoma or poorly differentiated carcinoma. Nodes, bone, liver and lung were the most frequently involved sites. In all, 79 patients received at least three courses of treatment; 26 patients received six courses or more. Six complete responses and 21 partial responses were observed, for a total of 27 of 102 ORs or 26.5% (95% confidence interval 18.2–36.1%). The median survival was 9 months and median progression-free survival was 4 months. Toxicity was moderate to severe, with 57.8% of patients experiencing grade III–IV haematological toxicity, mainly leucopenia. The regimen employed has shown activity in tumours of unknown primary site, but was associated with significant toxicity. Such toxicity may be considered unjustified, given the large proportion of patients with tumours not likely to respond. Efforts should therefore be addressed to identify predictors of response to chemotherapy, thus limiting aggressive treatment to those patients who could benefit from it.